Are We Alive When Islamic Banks Dominate?: Case Study In Indonesia - Raditya Sukmana; Heri Kusworo (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
Islam promotes justice in every aspect of life including in banking and finance. Shariah has to be the foundation for any banking transactions to ensure that any single party is not being unfairly treated or exploited. Interest based bank is certainly create unfairness and exploitation. In any cases only single party which get a lot of benefit. Hence islamic banking industry need to be developed so that its market share will increase significantly until it can reach the domination of the national banking assets. This paper aims to forecast when such condition will occur. Adopting a popular forecasting tool such as double exponential smoothing, this study will inform us when islamic banking market share will reach 50% out of total banking asset. The monthly data examined starts from January 2004 to may 2011. We use a single time series data which is islamic banking market shares whereby it is calculated from the islamic banking asset divided by total banking asset. the structure of this paper is as follows: after the introduction which describe the history and performance of Indonesian islamic bank, it discusses about the data and method used in this paper. Next section is on the description and analysis on the result obtained. Lastly is the conclusion where it recommends some policies required from the obtained result in which the optimist scenario would say that the domination of Islamic banks may occur in our grandchild generation